A study of acceptance on new media usage among corporate communication practitioners: the rise of Covid-19 pandemic / Wardatul Hayat Adnan and Mohammad Yaacob - Adnan, Wardatul Hayat; Yaacob, Mohammad (Centre For Media And Information Warfare Studies, 2021)
Corporate communication involves managing both internal and external activities related to communication within an organization. The rise of covid-19 pandemic in many of the industries has led corporate communication practitioners to work online. Therefore, in preparing to this situation, the acceptance of online platform is crucial. Covid-19 pandemic has changed the way people communicate in its day-to-day activities. The use of new media tools becoming a must compared to face-to-face conversations. Motivated by the extensive used of new media tools among individuals to communicate, this study investigated the acceptance and usage of new media for communication and collaboration among practitioners in corporate communication. This study employs a quantitative approach that depends on a correlational study. A cross-sectional survey consisting of four sections was conducted to collect data from practitioners within the corporate communication field. There are 248 respondents participated in this study. The present study employed four constructs to describe the expected performance and effort in new media, the influence of social media and its facilitating conditions. The Unified Theory of Acceptance and Use of Technology (UTAUT) was used to examine the relationship of the main constructs and the Statistical Package for the Social Science (SPSS) was used to perform data manipulation and analysis. Respondents provided their responses by perceiving the factors that influence the usage of new media amongst them. Results indicated that New Media Performance Expectancy (NMPE) and New Media Facilitating Condition (NMFC) are positively associated with Behavioral Intention in Corporate Communication (BICC) in using new media in corporate communication-related matters.